Frontispiece: Mononuclear Dysprosium Alkoxide and Aryloxide Single‐Molecule Magnets. Issue 28 (17th May 2021) - Parmar, Vijay S.; Mills, David P.; Winpenny, Richard E. P.
Abstract : Mononuclear lanthanide (Ln) complexes can be high‐performing single‐molecule magnets (SMMs). Recently, there has been an influx of mononuclear Ln alkoxide and aryloxide SMMs. Here, mononuclear Dy III alkoxide and aryloxide SMMs with coordination numbers up to eight are covered in detail, with additional brief overviews of Tb III, Ho III, Er III and Yb III SMMs. For more information, see the review by V. S. Parmar, D. P. Mills and R. E. P. Winpenny on page 7625 ff.